REGENERATION OF OLD CITY CENTER CASE STUDY OLD BAZAR IN ZAKHO CITY CENTER, KURDISTAN REGION- IRAQ - Raswol, Layla M.; Khorsheed, Jowan B. (Journal of Duhok University, 2017)
Zakho is one of the oldest towns in Iraqi Kurdistan Region. It is distinguished for its rich and diverse Architectural heritage. It has many cultural and historical sites and a city center that date back to the ancient time. The rapid urban development of the inner city has changed the historical character of the Old city with its cultural value. The additional new buildings have transformed the historical city area without any respect to its traditional structure and surrounding landscape. The main objectives of the research are protecting the architectural heritage and its historic value to bring life to Zakho old bazar as a case study, and regenerate the physical - and socio-economic environment through attractive mix use activities and public space. This research will firstly identify and analyze the existing heritage components in old Zakho Bazar, which require protection and development in different aspects. It will highlight the challenges facing the built-up area and the decline of the historic places. Furthermore, it will explain the importance of adopting the regenerating concept to balance between the dynamic urban development and the architectural conservation of historical and cultural heritage as well as improving the infrastructure and the built environment.